High-oxygen-permeability waterproof organic composite membrane, preparation method thereof and application of high-oxygen-permeability waterproof organic composite membrane in lithium-air battery

By integrating the PDMS film into the surface of the PIM-1 porous membrane, a highly oxygen permeable and waterproof organic composite membrane was developed, which solved the problem that the oxygen selective membrane in lithium-air batteries is difficult to balance between high power density and waterproof performance, and achieved stable operation and cycle life of lithium-air batteries in high current density and humid environments.

CN119581595APending Publication Date: 2025-03-07NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411343144.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The oxygen-selective membrane of existing lithium-air batteries is difficult to balance between high power density and waterproof performance, resulting in insufficient oxygen permeability and contamination of liquid components, affecting the cycle life of the battery.

Method used

By integrating the PDMS film onto the surface of the PIM-1 porous membrane, a highly oxygen permeable waterproof organic composite film was developed. This film effectively prevents H2O from eroding the battery while maintaining high oxygen permeability.

Benefits of technology

The stable operation of lithium-air batteries in high current density and humid environments is achieved, which extends the cycle life of the battery and improves the practicality of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581595A_ABST
    Figure CN119581595A_ABST
Patent Text Reader

Abstract

The invention discloses a high-oxygen-permeability waterproof organic composite membrane, a preparation method thereof and application of the high-oxygen-permeability waterproof organic composite membrane in a lithium-air battery, the high-oxygen-permeability waterproof organic composite membrane comprises a porous membrane and a PDMS membrane layer covering the surface of a porous substrate membrane, and the porous membrane is made of an intrinsic microporous polymer PIM-1. The membrane not only has high oxygen permeation rate, but also can effectively prevent H2O from corroding the battery. And the high oxygen permeation rate is combined with the remarkable hydrophobicity of PDMS, so that the operation stability of the lithium-air battery in a complex environment is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a highly oxygen-permeable and waterproof organic composite film, a preparation method thereof and application in a lithium-air battery, belonging to the technical field of lithium-air batteries. Background Art

[0002] In recent years, the requirements for increasing the energy density and reducing the cost of rechargeable batteries have pushed non-protonic lithium-air batteries to a new stage. Based on the reversible electrochemical reaction between lithium and O2, non-protonic lithium-air batteries can achieve ultra-high energy density, up to ~3500Wh kg -1 , 2-5 times higher than conventional lithium-ion batteries. This high energy density is enough to enable electric vehicles to travel 500 kilometers on a single charge, comparable to gasoline vehicles. Another advantage of lithium-air batteries is the ability to use air atmosphere as an oxygen source, eliminating the need for auxiliary oxygen tanks and promoting practical applications.

[0003] However, impurities in the air (mainly H2O and CO2) can react harmfully with the components of Li-air batteries (i.e., the lithium metal anode and the cathode active chemical Li2O2). The limited concentration of CO2 in the air and its solubility in the electrolyte restrict its reaction with Li and Li2O2. In addition, CO2 can form a protective coating on the interface of the lithium metal anode. Compared with CO2, the concentration of H2O in the air depends on the local relative humidity (RH). Commonly used organic electrolyte solvents such as dimethyl sulfoxide (DMSO) are quite hygroscopic, and the reaction between water and the lithium anode can produce hazardous H2. Therefore, H2O is the main harmful substance in the air and needs to be isolated from aprotic Li-air batteries.

[0004] The use of oxygen-selective membranes can isolate Li-air batteries from harmful H2O while allowing O2 from air to enter. However, developing OSMs for such Li-air batteries remains challenging because the kinetic diameter of H2O is O2 Much smaller. This means that H2O generally diffuses faster than O2 in bulk and Knudsen diffusion processes. Therefore, materials with a preferential affinity for O2 are used in oxygen selective membranes, such as silicone oil and fluoride. For example, Xie et al. prepared OSM by filling a porous Celgard membrane with perfluorinated polyether (PFPE) liquid. This composite OSM enables aprotic lithium-air batteries to operate at 100 mAg in ambient air. -1 The current density was stably maintained for 144 cycles.

[0005] Typically, the oxygen permeability of silicone oil / fluoride wetted oxygen selective membranes ranges from 0.49-59.4 Barrer, which is not high enough for aprotic lithium-air batteries that require high power density. In addition, these liquid components can be contaminated by electrolyte solvents and leak over long-term use. Summary of the invention

[0006] The purpose of the present invention is to provide a highly oxygen permeable and waterproof organic composite membrane, a preparation method thereof, and an application thereof in a lithium-air battery. By integrating a PDMS membrane onto the surface of a PIM-1 porous membrane, a membrane having dual functions of water resistance and oxygen permeability is obtained. The membrane has a high oxygen permeability of 6883.41 Barrer and can effectively prevent H2O from corroding the battery. The high oxygen permeability of the membrane plus the significant hydrophobicity of PDMS enhance its practicality.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A highly oxygen-permeable and waterproof organic composite membrane comprises a porous membrane and a PDMS membrane layer covering the surface of the porous substrate membrane, wherein the material of the porous membrane is an intrinsic microporous polymer PIM-1.

[0009] Preferably, the thickness of the PDMS membrane layer is ≤50 μm, and the thickness of the porous membrane is ≤150 μm.

[0010] The method for preparing any of the above-mentioned highly oxygen-permeable and waterproof organic composite films comprises the following steps:

[0011] S1, preparing PIM-1 and preparing a PIM-1 solution, casting and then drying to obtain a porous membrane;

[0012] S2, mixing the PDMS prepolymer and the curing agent to prepare a prepolymer solution, coating the prepolymer solution on the surface of the porous membrane and curing it to obtain the highly oxygen-permeable and waterproof organic composite membrane.

[0013] Preferably, in step S1, the preparation method of PIM-1 is: under the protection of nitrogen or inert gas, anhydrous potassium carbonate, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane and tetrafluoroterephthalonitrile are dispersed in a toluene-containing solvent, stirred and heated, and after the reaction is completed, PIM powder is precipitated.

[0014] Preferably, the mass ratio of anhydrous potassium carbonate, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, and tetrafluoroterephthalonitrile is (2-6):(1-4):(2-5);

[0015] The conditions for the heating reaction are: 110-170°C, 40-160min.

[0016] Preferably, the toluene-containing solvent is a mixture of toluene and at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

[0017] Preferably, in step S2, the mass ratio of PDMS prepolymer to curing agent is (8-15):1;

[0018] In the prepolymer solution, the mass ratio of the total mass of the PDMS prepolymer and the curing agent to the solvent is (8-12):1.

[0019] Preferably, in step S2, the coating is performed by spin coating, the rotation speed is 1000-5000 rpm, and the spin coating time is 0.5-3 min. The curing conditions are: under vacuum conditions, 70-100° C., and 1-6 h.

[0020] Application of any of the above-mentioned highly oxygen-permeable and waterproof organic composite membranes in lithium-air batteries.

[0021] A method for inhibiting electrolyte evaporation in a lithium-air battery is to use a composite membrane consisting of a porous membrane and a PDMS membrane layer covering the surface of the porous substrate membrane, wherein the material of the porous membrane is an intrinsic microporous polymer PIM-1;

[0022] The electrolyte is DMSO.

[0023] The beneficial effects of the present invention are:

[0024] Aiming at the problem that the oxygen permeability range of silicone oil / fluoride wetted oxygen selective membrane is low, and the liquid component will be contaminated by electrolyte solvent and leak during long-term use, the present invention solidifies silicone oil to prepare silicon-enhanced cured polydimethylsiloxane (PDMS) oxygen selective membrane for non-proton lithium-air batteries. Due to the cross-linked structure and high molecular weight, the cured PDMS-based oxygen selective membrane exhibits a high oxygen permeability (1638 Barrer), which is much higher than other oxygen selective membranes. At the same time, the waterproof performance of the oxygen selective membrane is still well maintained, and the cycle life of the lithium-air battery equipped with the oxygen selective membrane in ambient air exceeds 700 hours. However, although OSM has good oxygen permeability, an overly thick oxygen selective membrane will cause difficulty in battery discharge. Therefore, reducing the thickness of PDMS (about 430 μm) is crucial to improving the oxygen permeability of OSM.

[0025] Due to the highly flexible polymer backbone and weak intermolecular interactions, the stiffness of PDMS-based membranes is moderate. In order to prepare a free-standing PDMS membrane with sufficient mechanical strength, the thickness of the cured PDMS membrane is usually more than ~100 μm, but still relatively thick. A thin film composite (TFC) is a composite membrane structure that includes a thin layer located on top of a supporting porous substrate membrane. Using this membrane structure, the thickness of the PDMS membrane can be reduced to less than ~10 μm. In addition, good water resistance still applies to thin PDMS layers.

[0026] PIM is a new type of polymer composed of topologically ultra-rigid and twisted polymer chains, which can construct a large number of ultra-micropores (pore size < ). Such ultra-micropores in PIM not only have high gas permeability, but are also small enough to prevent the penetration of PDMS polymer for the preparation of thin-layer composite templates based on PDMS. In addition, PIM has good processing properties and film-forming ability, which is very valuable in microporous materials. Another consideration is the size of ultra-micropores in PIM compared to the free volume in PDMS. The same size.

[0027] The PIM / PDMS thin layer composite membrane for non-protonic lithium-air batteries prepared by the present invention is characterized by a thin PDMS layer (which can be less than 10 μm) and an ultra-microporous PIM-1 polymer substrate. The composite membrane combines the advantages of the two components, has an ultra-high oxygen permeability of 6883 Barrer and 132 GPU, and has an effective blocking effect on H2O in the air. The excellent performance of the PDMS / PIM-1 thin layer composite oxygen selective permeable membrane has inspired non-protonic lithium-air batteries in 2.0Ag -1 The current density is high under ambient air operation and at 1.0A -1 The current density was continuously increased for 90 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of PDMS / PIM-1TFC OSM for non-protonic Li-air batteries;

[0029] Figure 2 For FTIR analysis of the prepared PDMS and PIM-1;

[0030] Figure 3 is the H NMR spectrum of PIM-1 film;

[0031] Figure 4Figure 3 Porous structure, lamination morphology, and mechanical properties of PIM / PDMS TFC membranes. (a) 3D molecular model of PIM-1 segments, revealing voids of approximately 0.7 nm in size around the twisted site. Inset shows the appearance and flexibility of the PIM / PDMS-2500 TFC membrane. (b) N2 adsorption isotherm of PIM-1 substrate. Inset shows the corresponding pore size distribution (PSD) curve, indicating a peak pore size of approximately 0.6 nm. (c) AFM image of PDMS on the left side of the PIM / PDMS-2500 membrane and PIM-1 on the right side, evaluating the scan area roughness (Ra) of 1×1 μm. (de) Tensile stress-strain curves of a cured PDMS stand-alone membrane with a thickness of ~430 μm (top) and a PIM / PDMS-4500 TFC membrane with a total thickness of ~52 μm (bottom); (f) SEM image of the PDMS side surface of the PIM / PDMS-2500 membrane. (gi) Cross-sectional SEM images of PIM / PDMS-4500, PIM / PDMS-2500, and PIM / PDMS-1500 TFC membranes were obtained respectively;

[0032] Figure 5 is the thermogravimetric curve of PIM-1PIM / PDMS in air;

[0033] Figure 6 To evaluate the resistance of PIM / PDMS-2500 to H2O and electrolyte. (a) Oxygen permeability test of PIM / PDMS-2500. (b) Humidity adsorption experiment of PIM / PDMS-2500. The inset is the contact angle between H2O and PIM / PDMS-2500. (c) XRD images of unprotected and PIM / PDMS-2500 protected lithium anodes in ambient air. The inset shows the changes of Li after unprotected, PIM and PIM / PDMS-2500 encapsulation in ambient air with a humidity of 70% (the order in the figure is from left to right). (d) Schematic diagram of hydrophobic oxygen transfer of PDMS (left) and PIM (right). (e) DMSO was left standing in unprotected and PIM / PDMS-2500 protected glass bottles for 150h (standing at 100℃ for 0-100h, standing at 150℃ for 100-150h, and the rest of the conditions were exactly the same);

[0034] Figure 7 (a) Unprotected lithium and PIM / PDMS-2500 protected lithium were taken out of the dry glove box and digital photos were taken after standing for 30 seconds. (b) Digital photos of unprotected lithium and PIM / PDMS-2500 protected lithium were taken after a small amount of ultrapure water was dropped. The inset is a digital camera photo of the lithium sheet after the PIM / PDMS-2500 in the glove box was peeled off after the test;

[0035] Figure 8The changes of Li metal when the package is unprotected, PIM, and PIM / PDMS-2500 covered in an environment with an actual humidity of 70% (from left to right in the figure);

[0036] Fig. 9 The contact angles of DMSO on PIM (left area) and PIM / PDMS-2500 (right area);

[0037] Fig.10 The chemical stability of PDMS to DMSO solvent. Digital photos of PDMS soaked in DMSO solvent (left) at the beginning and (right) after 3 days. The mass loss of PDMS is 0.21 mg. The original mass of PDMS is 359.22 mg;

[0038] Fig.11 Evaluation of the rate performance of lithium-air batteries. (a) Rate performance of lithium-air batteries without protection and PIM / PDMS-2500 encapsulation. (b) Discharge medium voltage corresponding to each cycle. Evaluation of the long cycle life of lithium-air batteries. (c) Cycling curves of lithium-oxygen batteries and lithium-air batteries using Super P. (d) Initial full discharge capacity of lithium-air batteries when using PIM / PDMS-2500, PIM / PDMS-1500 or no membrane in ambient air (relative humidity 50%). Cycling performance curves of lithium-air batteries without protection (e), PIM encapsulation (f) and PIM / PDMS-2500 encapsulation (g) in ambient air with an ambient humidity of (35%);

[0039] Fig.12 This is the cathode FESEM image of the lithium-air battery without PIM / PDMS-2500 encapsulation after the first discharge;

[0040] Fig.13 (a) The discharge diagram of the Li-air battery wrapped in 1650 μm thick PDMS; (b) The cycling performance curve of the Li-air battery encapsulated in PIM / PDMS-1500 and (c) PIM / PDMS-4500 in ambient air with a humidity of 35±5%;

[0041] Fig.14(a), (b) EIS measurements of cells with and without PIM / PDMS-2500 in ambient air (relative humidity ~60%) at open circuit voltage (OCV) and (c) the corresponding time ohmic resistance. FESEM images of the anode of Li-air cells with (d) / without (e) PIM / PDMS-2500 encapsulation after the 10th discharge. (f) XRD images of the anode of Li-air cells encapsulated with or without PIM / PDMS-2500 after the 10th discharge. FESEM images of the cathode of Li-air cells with (g) / without (h) PIM / PDMS-2500 encapsulation after the 10th discharge. (i) XRD images of the cathode of Li-air cells with or without PIM / PDMS-2500 encapsulation after the 10th discharge. DETAILED DESCRIPTION

[0042] Non-protonic lithium-air batteries have become a promising energy storage device due to their ultra-high energy density. However, substances in the air that are not conducive to reaction, especially water, will cause non-protonic lithium-air batteries to decay rapidly during cycling. Traditionally, preventing water intrusion requires a dense and thick O2 selective membrane at the cathode, and O2 permeability is therefore limited. In order to break the balance between oxygen permeability and water permeability, the present invention proposes a new type of composite film structure, such as Figure 1 As shown in Figure 1, it includes a layer of polydimethylsiloxane (PDMS) with good water-repellent properties and an intrinsic microporous polymer (PIM-1) with high oxygen permeability. This composite film structure (PDMS / PIM-1) enables lithium-air batteries to operate at high current densities (1.0Ag -1 ) in ambient air (relative humidity: 35%) for 90 cycles, which is attributed to the ultra-high oxygen permeability (6883 Barrer) and effective water barrier of the oxygen selective membrane. This example analyzes and explains the selective transport of oxygen to water in the free volume and micropores. This pioneering work demonstrates the potential of high free volume / micropore polymers and TFC membrane structures in the development of new oxygen selective membranes for aprotic lithium-air batteries.

[0043] Material

[0044] 0.3 mm metallic lithium was purchased from Tianjin Zhongneng Company. Whatman GF / B glass fiber separator was purchased from Whatman Company, UK. Lithium bis(trifluoromethanesulfonyl)imide was purchased from Shanghai Aladdin Co., Ltd. Super P (SP carbon black catalyst) was purchased from Nanjing Pioneer Nanomaterials. Dimethyl sulfoxide (DMSO) was purchased from Alpha Reagents. CR2032 lithium-air battery housing was purchased from Colotech. Polytetrafluoroethylene emulsion was purchased from Dow Corning Reagents.

[0045] Preparation method of lithium-air battery composite oxygen permeable membrane

[0046] Preparation of self-microporous polymer (PIM-1) based membrane.

[0047] Anhydrous potassium carbonate (4.14 g), monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane (2.00 g) and tetrafluoroterephthalonitrile (3.40 g) were added into the flask under nitrogen protection, and then a mixed solution of organic solvent and toluene was added. After stirring evenly, the temperature of the flask was raised to 140°C. A water separator and a condenser were connected to the flask. The turbid liquid in the lower layer of the water separator was discharged in time, and the upper layer was kept with liquid reflux, otherwise 5 mL of toluene was added.

[0048] After 100 min of reaction, the mixture in the flask was poured into methanol to precipitate a fluorescent yellow solid, which was then soaked in a 0.1 M hydrochloric acid aqueous solution for 12 h and dissolved in chloroform at a concentration of 5 wt%. After centrifugation to remove the residue, the supernatant was reprecipitated in methanol to obtain PIM-1 powder (molecular weight M n About 40-100 kDa, molecular weight distribution about 1.2-2.5).

[0049] Prepare a 2wt% PIM-1 chloroform solution, degas by ultrasonic for 3 minutes, take 2-8mL of the solution and spread it evenly on a 6×6cm glass plate, and naturally evaporate and solidify in a closed box. Then, peel off the PIM-1 base film (film thickness is about 20-80μm) in methanol and vacuum dry it for later use.

[0050] The organic solvent is N,N-dimethylformamide (DMF), the volume of the organic solvent is preferably 20 mL, and the volume of toluene is preferably 10 mL.

[0051] Preparation of polydimethoxysiloxane (PDMS) thin layer.

[0052] Take PDMS prepolymer and curing agent and add them to a beaker in a mass ratio of 10:1. Stir mechanically for 5 minutes, and the rotation speed is preferably 800 rpm. Dissolve the obtained viscous liquid in an organic solvent, and the mass ratio of the organic solvent to the viscous liquid is 10:1. Vacuum degassing for 5 minutes, anchor the self-microporous polymer base membrane on the spin coater suction cup, drop and evenly spread the above solution, spin coat at 2500 rpm for 1 minute, remove the membrane and place it in a vacuum oven at 80°C for vacuum heat treatment for 6 hours to obtain a PIM / PDMS composite membrane with a PIM-1 membrane as the substrate and a PDMS thin layer.

[0053] The prepolymer and curing agent are preferably the basic components and cross-linking agent in the DC184 product of Dow Corning; and the organic solvent is n-hexane.

[0054] Composite oxygen permeable membrane battery performance test

[0055] In a glove box, SP carbon black catalyst and polytetrafluoroethylene (PTFE) adhesive emulsion were mixed into slurry at a mass ratio of 85:15, and the slurry was evenly coated on carbon paper with a diameter of 8 mm, and the catalyst loading was controlled to be 0.1 mg, as the positive electrode of the lithium-air battery; bistrifluoromethylsulfonyl imide lithium salt (LiTFSI) was dissolved in dimethyl sulfoxide (DMSO) with an electrolyte concentration of 1M, as the electrolyte of the lithium-air battery; a lithium sheet with a diameter of 10m and a thickness of 0.4μm was used as the negative electrode of the lithium-air battery; the above positive and negative electrodes were separated by Whatman glass fiber paper, and after adding the electrolyte, they were encapsulated in a button-type CR2032 battery shell, and 19 air holes were opened on the anode side of the battery shell. The gasket, oxygen permeable membrane, and orifice plate were placed on the battery shell in turn, and pressure was applied to assemble a battery as a whole, and connected to the battery test bench for charge and discharge cycle performance testing.

[0056] Oxygen permeability test of composite oxygen permeable membrane

[0057] The oxygen permeable membrane is placed in the middle of a membrane pool with cavities at both ends and tightly sealed; the cavity downstream of the membrane is evacuated to less than 1Pa, and a pure oxygen flow is introduced into the cavity upstream of the membrane, and the pressure is controlled to 0.2MPa by a back pressure valve; the pressure sensor downstream of the membrane records the cavity pressure change in real time, and when the pressure rise rate stabilizes, the oxygen permeability P (Barrer, 1Barrer = 10 -10 cm 3 (STP) cm cm -2 s -1 cmHg -1 ):

[0058]

[0059] Where V is the cavity volume (cm 3 ), l is the thickness of the oxygen permeable membrane (cm), A is the effective test area (cm 2 ), T0 and T are the test temperature (273K) and standard temperature (303K), respectively. f and p0 are the test pressure difference (Pa) and standard pressure (76 cmHg), respectively. p / d t is the pressure rise rate (Pa s -1 Based on the test results listed in Table 1, the oxygen permeability of PIM / PDMS-2500 is 215 GPU (1.28×10 -9 mol m 2 s -1 Pa -1 ).

[0060] Table 1 Oxygen permeability measurement of PIM / PDMS-2500

[0061]

[0062] Figure 2 The ATR-FTIR spectra in the preliminarily verified the chemical structures of PDMS and PIM-1 polymers. The 1H-NMR results of PIM-1 ( Figure 3 ) further showed the exact characteristic peaks consistent with the literature. The molecular weight (Mw) of PIM-1 polymer was ∼74 kDa and the polydispersity was ∼1.7, which ensured the film-forming ability of PIM-1 substrate. The porous structure of PIM-1 substrate was characterized by N2 isotherm adsorption at 77 K, as shown in Figure 4 As shown in area b in the middle, the adsorption curve of PIM-1 increases sharply at a lower relative pressure, indicating that PIM-1 has abundant micropores. The specific surface area of ​​the PIM-1 substrate is as high as 787 m 2 g -1 The corresponding pore size distribution (PSD) shows that it is a hierarchical porous structure with a peak pore size of ~0.6 nm, which meets the standard of ultra-micropores. Figure 4 As shown in region a, the helical unit of the PIM-1 segment provides a twisted topology, while the other dioxane bond unit strongly restricts any rotation of the polymer backbone, preventing the occupation of the twisted voids during the filling process, thereby generating ultramicropores in PIM-1.

[0063] A thin PDMS layer was prepared on a PIM-1 substrate by spin coating and subsequent thermal curing. Freestanding PIM / PDMS composite membranes with visible flexibility were obtained. The thickness of the PDMS layer was controlled by adjusting the rotation speed to 1500, 2500, and 4500 revolutions per minute (rpm). The morphologies of the prepared PIM / PDMS-1500, PIM / PDMS-2500, and PIM / PDMS-4500 TFC membranes were characterized. Figure 4 The surface SEM image of the PDMS side, shown in region f, shows that the PDMS coating on the PIM-1 substrate has no defects. Figure 4 As can be seen in the g, h, and i regions, the PDMS layer thickness of each PIM / PDMS TFC membrane is ∼6.1 μm, 9.3 μm, and 20.9 μm, respectively, which is much lower than the PDMS layer thickness reported previously. The roughness of the PIM-1 surface is slightly higher than that of the PDMS surface, which can be seen from their AFM images ( Figure 4 (c area). Figure 4In the middle d and e regions, the mechanical properties of the PIM / PDMS-2500 composite membrane and the cured PDMS independent membrane are compared. Due to the increase in the stiffness of the PIM-1 matrix, the elongation at break of the film decreases, but the tensile strength increases from 2.4 MPa to 26.5 MPa. According to the thermogravimetric curve of the PIM / PDMS TFC membrane in air ( Figure 5 ), when the initial decomposition temperature reaches ∼284 ​​°C, the thermal stability of the PIM / PDMS TFC membrane is also acceptable.

[0064] In order to better provide an environment similar to that of lithium-oxygen batteries, oxygen must penetrate the membrane as efficiently as possible and interact with the cathode. Using the gas permeation equation, the oxygen permeability of PIM / PDMS-2500 was calculated to be 6883.41 Barrer ( Figure 6 This value significantly exceeds that reported in previous literature (Table 2), highlighting the excellent oxygen permeability of the membrane and its potential to enhance the performance and stability of lithium-air battery systems.

[0065] Table 2 Comparison of O2 permeability with previously reported oxygen permeable membranes

[0066]

[0067] Through experimental observation, it was found that even the microporous PIM-1 membrane has a certain waterproof ability. Considering the free volume of PDMS Ultra-micropores with PIM-1 , it is believed that their O2 / H2O separation mechanisms have some similarities. PDMS, PIM-1 and other well-known OSM materials such as fluoride and polyethylene are hydrophobic. From the perspective of intermolecular interactions, hydrophobicity means that the interaction between two H2O molecules is greater than the interaction between H2O and the surface groups of the subject. For PDMS and PIM-1, their hydrophobicity comes from their abundant methyl or methylene groups. Although water exists in a gaseous state in the air, the adsorption state of water on the solid surface is much more compressed, a bit like a liquid or solid. Due to the strong and unique interactions between water molecules, especially the hydrogen bonds between water molecules, the adsorption of water on hydrophobic surfaces tends to obey multilayer adsorption behavior. However, for those polymers with only free volume or ultra-micropores, several adsorption layers can easily occupy the pores / voids, thereby encountering very strong capillary repulsion, preventing the advancement of water groups. This can explain the PIM-1 membrane ( Figure 6 The reason why the water absorption volume of other reported hydrophobic MOFs is much smaller than the equivalent pore volume is that from the perspective of the diffusion process in the membrane, such as Figure 6As shown in the middle d area, the H2O molecules adsorbed in the water clusters in the membrane must overcome strong interactions, namely hydrogen bonds, to diffuse through narrow channels, while the interactions of O2 molecules are relatively weak and have little effect on diffusion. The only way for water molecules to pass through these membranes is through the adsorption and diffusion of single water molecules, which is unlikely. Therefore, it is believed that this nano-confinement effect surrounded by a hydrophobic surface can explain the remarkable O2 / H2O separation ability of PDMS and PIM-1 materials. The porosity of PIM-1 is about 17 vol%. The humidity adsorption experiment of PIM-1 is shown in Figure 6 As shown in the b area. The adsorption of humidity at a certain humidity is only less than 4wt% (even less than 1wt% at 60% RH), which is much lower than the increase in adsorption after filling H2O in the PIM pores (about 15wt%), indicating that it is difficult for H2O molecules to enter the pores of PIM-1. Moreover, the adsorption-desorption curves in the figure basically overlap, indicating that H2O is only adsorbed along the channel surface and no condensation occurs inside the channel. The H2O contact angle on PIM is 94.0°, while that on PIM / PDMS-2500 is 115.7° ( Figure 6 (inset in region b). This increase is due to the fact that PDMS is an effective water-repellent material that, when coated on the surface of PIM-1, enhances the composite membrane’s resistance to liquid H2O. However, contact angle measurements only indicate resistance to liquid H2O. In ambient air, gaseous H2O is more likely to penetrate the membrane material and enter the cell. Figure 7 As shown, to verify the effectiveness of the membrane in blocking gaseous H2O, PIM / PDMS-2500 was applied to the lithium surface using vacuum ester in a glove box filled with dry Ar atmosphere. The other group did not use any membrane protection. In ambient air with a humidity of 70%, the surface of the unprotected lithium sheet turned black shortly after it was taken out of the glove box. When a small amount of water was introduced to the lithium surface, the untreated lithium reacted violently to produce a white solid powder. In contrast, H2O droplets still remained on the surface of PIM / PDMS-2500. After removing the PIM / PDMS-2500 in the glove box, the lithium surface retained its metallic luster, indicating that the membrane effectively prevented the intrusion of H2O.

[0068] To evaluate the hydrophobicity of the membranes, an additional experiment was performed. Two lithium samples of uniform thickness were placed in glass bottles, covered with PIM and PIM / PDMS-2500 membranes, respectively. Silicone was applied between the bottle mouth and the membrane to ensure a tight seal. For comparison, an unprotected lithium sample was placed in an open glass bottle. After removal from the glove box, the unprotected lithium began to turn black after about 30 seconds ( Figure 8). After 10 minutes, the area around the unprotected lithium turned black, and the PIM-protected lithium also showed signs of blackening. However, after 30 minutes, the PIM / PDMS-2500-encapsulated lithium still maintained its metallic luster at 70% humidity, while the unprotected lithium sheet turned completely black, and the PIM-encapsulated lithium showed obvious evidence of water corrosion. X-ray diffraction analysis further confirmed that the lithium metal encapsulated with PIM / PDMS-2500 showed a clear lithium metal peak, while the unprotected lithium showed a clear LiOH peak, indicating a large amount of water-induced corrosion ( Figure 6 This experiment demonstrates that the PIM / PDMS-2500 membrane has excellent hydrophobicity and protective properties under humid conditions.

[0069] In order for a membrane to be effectively utilized in a lithium-air battery system, it must provide more than just hydrophobicity. Equally critical is the membrane's ability to suppress electrolyte evaporation. Dimethyl sulfoxide (DMSO) is a relatively stable solvent that resists superoxide anion radicals and has been widely used in Li-O2 batteries. However, the DMSO solvent is volatile at room temperature and is rapidly depleted in an open lithium-air battery. The contact angles of DMSO on PIM and PIM / PDMS-2500 were determined to be 65.0° and 85.0° ( Fig. 9 ). PDMS was immersed in DMSO solvent for 3 days. After immersion, no significant change was observed in the mass after drying ( Fig.10 ). The results show that PIM / PDMS-2500 is not easily dissolved by DMSO vapor during the cycle. To further confirm the efficacy of the membrane in blocking DMSO vapor, experiments were conducted in a glove box under a dry argon atmosphere ( Figure 6 middle e area).

[0070] 4 ml of pure DMSO solution was placed in a glass bottle, one without any membrane and the other sealed with a PIM / PDMS-2500 membrane. DMSO evaporated slowly in argon from 0 to 100 hours at room temperature. In the absence of a membrane, the DMSO volatilization rate was about twice that of the PIM / PDMS-2500 protected sample. Specifically, after 24 hours, the unprotected sample lost 0.0119 g DMSO, while the PIM / PDMS-2500 protected sample lost about 0.0054 g. Subsequently, the temperature was increased to 60 ° C and maintained for another 50 hours. During the heating period, the sample without the PIM / PDMS-2500 membrane lost 0.2493 g DMSO, while the sample protected by the PIM / PDMS-2500 membrane only lost 0.0217 g, less than one-tenth of the unprotected sample (Table 3).

[0071] Table 3 Comparison of DMSO volatilization loss (when the protective film is PIM or PIM / PDMS-2500)

[0072]

[0073] In the previous description, the waterproof, oxygen-permeable and DMSO-blocking capabilities of PIM / PDMS-2500 have been demonstrated by some methods. To further verify these functions, the membrane was tested on an assembled coin cell. In general, the oxygen permeability of the membrane is closely related to the rate performance of the battery. When the oxygen supply is sufficient, the battery can switch seamlessly between high and low current densities. In a humid environment with a humidity of 60%, tests were performed at different current densities of 500-1000mAg1 and 2000mAg1 (limiting capacity of 1000mAh g1) ( Fig.11 The cells effectively protected by the PIM / PDMS-2500 membrane maintained overall stability throughout the cycling process. In contrast, the unprotected cells discharged below 2V in both cycles and stopped working completely after 60 hours. This result highlights the excellent oxygen permeability of the PIM / PDMS-2500 membrane and its significant improvement in battery performance.

[0074] In order to more intuitively observe the effect of PIM / PDMS-2500 on the battery in ambient air, Super P was used as the cathode and Li-air batteries were assembled at a relative humidity of ∼35%. The cut-off capacity was 1000 mA h g -1 , the cut-off voltage window is 2.0~5.0V, and the current rate is 1A -1 . Fig.11 The e, f, and g regions in the middle show the relationship between specific capacity and voltage during the cycle of PIM / PDMS-2500 without membrane protection. It can be clearly seen that the discharge voltage of the Li-air battery without membrane protection reaches 2.74V in the first cycle, which is close to the discharge voltage of the Li-O2 battery. This is because without membrane protection, oxygen is almost not blocked from entering the battery, and the exposure time in the air during the first cycle discharge is short, so the lithium sheet is not seriously corroded. From the FESEM image, the product is still mainly Li2O2 ( Fig.12 ). Without any protection, the battery will quickly decay and die due to the corrosion of H2O, and can only run 11 times (22h) at the discharge voltage. The battery protected by PIM and PIM / PDMS-2500 can last for 62h and 180h respectively, although the first discharge voltage is less than 2.74V. The superposition of life shows that the PIM and PDMS protection layers extend the life. Even under the condition of pure oxygen with the same current density, the cutoff capacity is 1000mA h -1 , lithium oxygen batteries can only run for about 170 hours ( Fig.11The experimental results are close to those of PIM / PDMS-2500. Practice has shown that PIM / PDMS-2500 can make lithium-air batteries work in humid environments like lithium-oxygen battery test devices.

[0075] The oxygen permeability of PDMS is closely related to its thickness. The PIM / PDMS Li-air battery (PDMS thickness is about 1000μm) was assembled under the condition of relative humidity of about 35%. The cut-off capacity is 1000mA hg -1 , the cut-off voltage window is 2.0~5.0V, and the current rate is 1A -1 .like Fig.13 As shown in the a region, the discharge voltage decays rapidly to 2.0 V. The thick PDMS film leads to insufficient oxygen permeation, which limits the application scenarios of lithium-air batteries. PIM / PDMS-1500 and PIM / PDMS-4500 lithium-air batteries were assembled under the same conditions. Fig.13 As shown in the b and c regions, the protected batteries can cycle for 116 hours and 154 hours respectively. Compared with the pure PIM protected battery, the cycle time of both is greatly increased, reflecting the excellent protection ability of PDMS.

[0076] Lithium-air batteries have extremely high specific energy, but in ambient air, the lithium sheet is corroded into LiOH and Li2CO3 due to the interference of impurities such as H2O. In ambient air with a relative humidity of 50%, the initial discharge capacity of LAB without adding PIM / PDMS-2500 is only 2610.19 mAh g -1 , while the initial discharge capacity of LAB with PIM / PDMS-2500 added is 10629.41 mAh g -1 , indicating that PIM / PDMS-2500 resists the invasion of H2O. It should be noted that although the cycle time of PIM / PDMS-1500 (154 h) is similar to that of PIM / PDMS-2500 (180 h), at a current density of 500 mAg -1 In the case of PIM / PDMS-1500, the long-term discharge platform is significantly lower than that of PIM / PDMS-2500. The oxygen permeability test results also show that there is a certain gap between PIM / PDMS-1500 and PIM / PDMS-2500, so the PDMS of about 10μm is determined to be the most suitable loading thickness.

[0077] The successful slowing down of H2O from the O2 cathode of Li-air batteries was further confirmed by comparing the resistance of the air (O2) cathode of Li-air batteries assembled with PIM / PDMS-2500 and without PIM / PDMS-2500 in a humid environment. Electrochemical impedance spectroscopy (EIS) can be used to measure the charge transfer resistance (Rct), the interfacial resistance (Rint) between the liquid electrolyte and the lithium metal electrode, and the ohmic resistance (Re). To investigate these parameters, coin-type Li-air cells with and without PIM / PDMS-2500 protection were assembled and impedance measurements were performed at 60% humidity for 12 hours, 48 ​​hours, and 100 hours. Electrochemical impedance spectroscopy (EIS) was used to monitor the changes in the impedance of the Li-air battery. An equivalent circuit was established for quantitative analysis of the Nyquist plot.

[0078] from Fig.14 It can be seen from the middle ab region that the simulated curve (solid line) fits well with the measured Nyquist plot (scattered circles) of the Li-air battery with and without PIM / PDMS-2500 in the outer shell (19 holes). The main parameters obtained from the measured Nyquist curve fitting are shown in Table 4. Under the protection of PIM / PDMS-2500, the R int In sharp contrast, during the same period, the R int The R of the PIM / PDMS-2500 protected battery increased from 3.48Ω to approximately 2250Ω, indicating that electrolyte volatilization was the main factor in the subsequent failure of the unprotected battery. ct The value of R increased slightly from 15.98Ω to 216.7Ω and 398.3Ω. In contrast, under the same conditions, the R ct The values ​​increased significantly from 498.2 Ω to 1083 Ω and 5157 Ω, indicating that the production of insulating materials such as LiOH caused difficulties in charge transfer.

[0079] Fig.14 The area (d) in the middle is the FESEM image of unreacted lithium. Fig.14 Figure e shows the FESEM image of the Li anode obtained from the assembled Li-air battery after 10 discharge cycles in a humid O2 environment, showing the XRD diffraction peak at 2θ (32.5°), corresponding to the LiOH (101) surface ( Fig.14 middle f area). Fig.14The middle gh region shows FESEM images of the cathodes of Li-air batteries assembled with and without PIM / PDMS-2500 membranes after a single discharge cycle in humid O2. The cathode of the unprotected Li-air battery exhibits a large number of lamellar structure discharge products, while the cathode of the battery with PIM / PDMS-2500 protection exhibits ring-shaped structure discharge products. Further characterization by XRD, such as Fig.14 These observations are supported by the XRD diffraction peak at 2θ (32.5°) observed in the absence of PIM / PDMS-2500, corresponding to the LiOH (101) surface. In contrast, the PIM / PDMS-2500 film showed distinct diffraction peaks at 2θ (32.8°) and (34.8°), indicating the (200) and (201) planes of Li2O2, respectively. These results highlight the effectiveness of the PIM / PDMS-2500 film in alleviating the impedance increase and enhancing the stability of lithium-air batteries in humid environments.

[0080] Table 4 Parameters obtained by EIS curve fitting

[0081]

[0082] In summary, the present invention has developed a membrane with dual functions of water resistance and oxygen permeability by integrating an ultrathin PDMS membrane onto the surface of PIM-1. Comprehensive characterization shows that the membrane effectively prevents H2O from corroding the battery while having a high oxygen permeability of 6883.41 Barrer. The present invention represents the first application of PIM-1 in the field of lithium-air batteries. The high oxygen permeability of the composite membrane, coupled with the significant hydrophobicity of PDMS, enhances its practicality. Using PIM / PDMS-2500 as a protective barrier, the lithium-air battery can be used under ambient conditions (current density of 1000mAg -1 , cut-off capacity is 1000mAh g -1 ) Stable cycle for 180 hours.

[0083] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A highly oxygen permeable waterproof organic composite membrane, characterized in that: The invention comprises a porous membrane and a PDMS membrane layer covering the surface of the porous substrate membrane, wherein the material of the porous membrane is an intrinsic microporous polymer PIM-1.

2. The highly oxygen-permeable waterproof organic composite membrane according to claim 1, characterized in that: The thickness of the PDMS film layer is ≤50 μm.

3. The method for preparing a highly oxygen-permeable waterproof organic composite membrane according to any one of claims 1 to 2, characterized in that: The steps include: S1, preparing PIM-1 and preparing a PIM-1 solution, casting and then drying to obtain a porous membrane; S2, mixing the PDMS prepolymer and the curing agent to prepare a prepolymer solution, coating the prepolymer solution on the surface of the porous membrane and curing it to obtain the highly oxygen-permeable and waterproof organic composite membrane.

4. The method for preparing a highly oxygen-permeable and waterproof organic composite membrane according to claim 3, characterized in that: In step S1, the preparation method of PIM-1 is as follows: under the protection of nitrogen or inert gas, anhydrous potassium carbonate, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane and tetrafluoroterephthalonitrile are dispersed in a toluene-containing solvent, stirred and heated, and after the reaction is completed, PIM powder is obtained by precipitation.

5. The method for preparing a highly oxygen-permeable and waterproof organic composite membrane according to claim 4, characterized in that: Anhydrous potassium carbonate, The mass ratio of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane and tetrafluoroterephthalonitrile is (2-6):(1-4):(2-5); The conditions for the heating reaction are: 110-170°C, 40-160min.

6. The method for preparing a highly oxygen-permeable waterproof organic composite membrane according to claim 4, characterized in that: The toluene-containing solvent is a mixture of toluene and at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

7. The method for preparing a highly oxygen-permeable waterproof organic composite membrane according to claim 3, characterized in that: In step S2, the mass ratio of PDMS prepolymer to curing agent is (8-15):1; In the prepolymer solution, the mass ratio of the total mass of the PDMS prepolymer and the curing agent to the solvent is (8-12):

1.

8. The method for preparing a highly oxygen-permeable waterproof organic composite membrane according to claim 3, characterized in that: In step S2, the coating is performed by spin coating, the rotation speed is 1000-5000 rpm, and the spin coating time is 0.5-3 min; The curing conditions are: under vacuum conditions, 70-100°C, 1-6h.

9. Use of the highly oxygen-permeable and waterproof organic composite membrane according to any one of claims 1 to 2 in lithium-air batteries.

10. A method for inhibiting electrolyte evaporation in a lithium-air battery, characterized in that: The composite membrane is composed of a porous membrane and a PDMS membrane layer covering the surface of the porous substrate membrane, wherein the material of the porous membrane is an inherent microporous polymer PIM-1; The electrolyte is DMSO.